2023
DOI: 10.3390/su15118879
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the Use of Active Compounds Obtained from Lavender

Ana-Maria Tăbărașu,
Dragoș-Nicolae Anghelache,
Iuliana Găgeanu
et al.

Abstract: Lavender is among the medicinal and aromatic plants with high economic value in the food, pharmaceutical, cosmetic and aromatherapeutic industries, and in its composition has numerous compounds, such as tannins, anthocyanins, minerals, saponins, flavonoids, polyphenols, essential oil and others. The qualitative and quantitative characteristics of lavender are best highlighted by extraction techniques such as hydrodistillation, steam distillation and supercritical CO2 extraction. In the water distillation extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…At the same time, using a statistical cluster analysis diagram, it was shown that there is a relationship between the antimicrobial activities and the presence of specific phenolic compounds in the extracts. According to Tăbăraşu et al [3], the quantity and quality of phenolic compounds in the plant material depends on both the ambient temperature, the season, the nutrients in the soil, and the anatomical part of the plant. The total phenol content in the leaf extracts was 31.64 mg GAE/g and was less than half that of the flowers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, using a statistical cluster analysis diagram, it was shown that there is a relationship between the antimicrobial activities and the presence of specific phenolic compounds in the extracts. According to Tăbăraşu et al [3], the quantity and quality of phenolic compounds in the plant material depends on both the ambient temperature, the season, the nutrients in the soil, and the anatomical part of the plant. The total phenol content in the leaf extracts was 31.64 mg GAE/g and was less than half that of the flowers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the oil, compounds such as tannins, phenolic acids, flavones, anthocyanidins, saponins, polyphenols, and minerals have been identified in the chemical composition of the plant. According to Tăbăraşu et al [3], essential oil can contain up to 300 different compounds, the qualitative and quantitative composition of which depends on the species, morphological part of the plant, and environmental factors affecting yield. Barbieri and Borsotto [4], in their research, indicate that younger plants synthesize more essential oil than older plant seedlings.…”
Section: Introductionmentioning
confidence: 99%